1998
DOI: 10.1109/36.718864
|View full text |Cite
|
Sign up to set email alerts
|

Automatic contrail detection and segmentation

Abstract: Automatic contrail detection is of major importance in the study of the atmospheric effects of aviation. Due to the large volume of satellite imagery, selecting contrail images for study by hand is impractical and highly subject to human error. It is far better to have a system in place that will automatically evaluate an image to determine 1) whether it contains contrails and 2) where the contrails are located. Preliminary studies indicate that it is possible to automatically detect and locate contrails in Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Researching global cloud and aerosol properties, radiative energy balance, 3D cloud morphology, and infectious disease risk due to climate fluctuations highlighted the importance of studying contrails’ effects on radiative balance and cloud formation in various contexts. The proposed multistep protocol for contrail detection and segmentation in AVHRR images shows promise in identifying contrail properties yet acknowledges challenges in detecting certain types and improving algorithm precision [ 15 ]. The study also revealed that converting the RGB color space to HSV enhanced segmenting satellite images, indicating the practical utility of color space transformations in this context [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…Researching global cloud and aerosol properties, radiative energy balance, 3D cloud morphology, and infectious disease risk due to climate fluctuations highlighted the importance of studying contrails’ effects on radiative balance and cloud formation in various contexts. The proposed multistep protocol for contrail detection and segmentation in AVHRR images shows promise in identifying contrail properties yet acknowledges challenges in detecting certain types and improving algorithm precision [ 15 ]. The study also revealed that converting the RGB color space to HSV enhanced segmenting satellite images, indicating the practical utility of color space transformations in this context [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…The analysis of clouds and their features is important for a wide variety of applications. It has been used for now casting to deliver accurate weather forecasts [14], rainfall, and satellite precipitation estimates [15], in the study of contrails [21], and various other day-to-day meteorological applications [7,16]. For cloud cover estimation, cloud detection plays a vital role, which classifies each pixel of all-sky images into clear sky element or cloud.…”
Section: Feature Extraction and Image Segmentationmentioning
confidence: 99%
“…Skeletons of linear structures are an important representation in the human visual systems. Ridge detection (also known as linear delineation [5]) has applications in medical imaging [5], remote sensing [20], photogrammetry [4], and other areas.…”
Section: Thinningmentioning
confidence: 99%